Tobacco Transcription Factor NtbHLH123 Confers Tolerance to Cold Stress by Regulating the NtCBF Pathway and Reactive Oxygen Species Homeostasis - Zhao, Qiang; Xiang, Xiaohua; Liu, Dan; Yang, Aiguo; Wang, Yuanying (Frontiers in Plant Science, 2018)
Cold stress is a major environmental factor that impairs plant growth and development, geographic distribution, and crop productivity. The C-repeat binding factor (CBF) regulatory pathway has an essential role in the response to cold stress. Here, we characterized a bHLH transcription factor from Nicotiana tabacum, NtbHLH123, in response to cold stress (4°C). Overexpression of NtbHLH123 enhanced cold tolerance in transgenic tobacco plants. Based on yeast one-hybrid, chromatin immunoprecipitation PCR, and transient expression analysis assays, NtbHLH123 binds directly to the G-box/E-box motifs in the promoter of the NtCBF genes and positively regulates their expression. Furthermore, NtbHLH123-overexpressing plants showed lower electrolyte leakage, reduced malondialdehyde contents, H2O2 and ROS accumulation under cold stress, which contributed to alleviating oxidative damage to the cell membrane after cold stress treatment. And NtbHLH123 increased stress tolerance by improving the expression of a number of abiotic stress-responsive genes to mediate the reactive oxygen species (ROS) scavenging ability and other stress tolerance pathways. Taken together, we present a model suggesting that NtbHLH123 is a transcriptional activator that functions as a positive regulator of cold tolerance by activating NtCBF, ROS scavenging-related, and stress-responsive genes.